Incidence of pelvic inflammatory disease in females presenting with low backache in orthopedic OPD - Deshpande, Juhi; Singh, Chanchal Kumar (International Journal of Research in Medical Sciences, 2022)
Background: Low backache (LBA) is one of the major global public health problems. It causes great disability and distress among females and hampers their day-to-day activities. Pelvic inflammatory disease (PID) is one of the major causes for LBA. Early diagnosis and treatment of PID leads to significant improvement in symptoms of LBA and prevents complications related to PID. The aim of the study was to determine the incidence of pelvic inflammatory disease (PID) in females attending orthopaedics OPD with complaints of low backache (LBA). Methods: A prospective epidemiological study was done on 200 female patients attending orthopedics OPD. Detailed history was taken followed by thorough examination. Patients were interviewed regarding their age, parity, demographic parameters, associated complaints, type of contraceptive use and addiction status. Results: Out of 200 female patients with LBA, PID was found in 55 (27.5%) patients. Majority (37%) of patients were from the age group of 40-49 years. 65% of patients were of low socio-economic status, 75% females were illiterate, 63.5% females were obese, 28% females were addicted to smoking, 24% tobacco chewing and 76.5% were parous. 53% of patients complained of discharge per vaginum. 42.5% females used oral contraceptive pills and 25.5% females had an intrauterine contraceptive device inserted. Conclusions: The study suggests that PID is a major contributing factor of LBA in female. Therefore, gynecological opinion should be taken for the complete management of LBA among females.